2018
DOI: 10.1093/ndt/gfx342
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-volume online haemodiafiltration on nutritional status and body composition: the ProtEin Stores prEservaTion (PESET) study

Abstract: OL-HDF for 1 year compared with HF-HD preserved muscle mass, increased protein intake and reduced the inflammatory state related to uraemia and dialysis, supporting the hypothesis that high convection volume can benefit nutritional status and prevent protein-energy wasting in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
3
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 51 publications
2
33
3
6
Order By: Relevance
“…subclinical chronic inflammation, which is not irrelevant, these values being still associated with increased mortality risk [12,17]. The effect on the inflammatory biomarkers may be due to higher convection volume achieved with MID leading to enhanced convective clearance of middle molecules [18,31]. According to the "reverse" configuration of the dialyzer [25], we can postulate that the amount of convection volume in post-dilution mode achieved in MID is closer to therapeutic goals currently recommended (> 23 L/session) [7][8][9][10], and are greater than that obtained by means of HDF in post-dilution mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…subclinical chronic inflammation, which is not irrelevant, these values being still associated with increased mortality risk [12,17]. The effect on the inflammatory biomarkers may be due to higher convection volume achieved with MID leading to enhanced convective clearance of middle molecules [18,31]. According to the "reverse" configuration of the dialyzer [25], we can postulate that the amount of convection volume in post-dilution mode achieved in MID is closer to therapeutic goals currently recommended (> 23 L/session) [7][8][9][10], and are greater than that obtained by means of HDF in post-dilution mode.…”
Section: Discussionmentioning
confidence: 99%
“…The survival benefit may at least in part depend on the modulation of chronic inflammation [11][12][13][14][15][16][17], and the associated improvement of nutritional status [18], consequent to increased convective volume. Indeed, Canaud et al [17] reported that C-Reactive Protein (CRP) decreases at higher convection, up to at least 25 L per session, even after adjustment for main confounders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high convection and substitution volumes can be reached safely with on-line HDF (OL-HDF), and OL-HDF is able to markedly enhance the removal of middle molecular substances. There are reports of several clinical advantages of OL-HDF, including the reduction of intra-dialytic hypotension [1], improvement of inflammation and oxidative stress [2], maintenance of better nutritional conditions [3], and improved survival [4][5][6]. Performance of OL-HDF with substitution fluid reinfusion in predilution or postdilution mode is a common clinical practice in HD centers.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of HDF have been ascribed to negative thermal balance due to the infusion of relatively cool substitution fluid. Interestingly, a recent prospective study showed that compared to high-flux HD, high-dose HDF was associated with preservation of muscle mass, increased protein intake and reduced inflammation, suggesting that HDF could help prevent protein-energy wasting [35].…”
mentioning
confidence: 99%